Rare nodular malignant melanoma of the heel in the Caribbean: A case report - Warner, Wayne A. (Int J Surg Case Rep, 2016)
INTRODUCTION: Malignant melanoma of the heel is a rare melanoma subtype with incidence rates that reflect the complex relationship between sun exposure at certain geographic locations, individual melanin levels and overall melanoma risk. It is oftentimes characterized by poor prognosis because of delays in presentation resulting in longitudinal tumor invasion, lymph node involvement and metastasis. PRESENTATION OF CASE: A 59-year-old woman was admitted to the Eric Williams Medical Sciences Complex, Trinidad and Tobago with a 5 mm pruritic lesion on her left heel. At presentation, the lesion was asymmetric with border irregularities, color heterogeneity, with dynamics in elevation and overall size. She was subsequently diagnosed with malignant melanoma with left inguinal lymphadenopathy. A single stage wide local excision (WLE) of the left heel lesion with a split-thickness skin graft (STSG) and a left inguinal lymphadenectomy were performed. Dacarbazine (Bayer) was administered post operatively. DISCUSSION: Globally, the incidence of malignant melanoma is rapidly increasing, particularly, in countries like Trinidad and Tobago with a significant population of non-fair skinned individuals. There is need for strategic initiatives to increase patient adherence in these populations. CONCLUSION: The rarity of malignant heel melanomas heightens the need for increased patient awareness and greater clinical surveillance to ensure early diagnosis and treatment.